Avaliação laboratorial da resistência ao cisalhamento de discos de porcelana e de um polímero de vidro cimentados à dentina bovina com o emprego de cimentos adesivos - Huhtala, Maria Filomena Rocha Lima [UNESP] (1999)
The aim of this study was to investigate the effectiveness of three luting agents : Resin Cement (3M), Variolink (Vivadent) e Fuji Plus (GC Coorp.); in bonding porcelain (Fortune, Williams) and glass polymer (Artglass, Kulzer) discs. To bovine dentin. The facial surfaces of 120 bovine incisors, previously mounted in self-cured resin, were ground flat on wet 80-grit SiC paper. Dentin surfaces exposed had their final finish accomplished by grinding on wet 240, 400 and 600-grit SiC paper. The specimens were randomly assigned to test groups of ten samples. Onto the pretreated dentin surfaces, the discs (5mm diameter,3mm height) were cemented Jhey were seated to a standardized luting thickness of 40µ. Each two groups were cemented with the same luting agent, and one of them shear tested after 24 h and the other after 180 days in an Instron machine. The bond strength data obtained were analysed by ANO VA and the Tukey test, 5%. The mode of failure was classified. The shear test results indicated significant differences among the luting agents: Variolink II (6, 02MPa), Fuji Plus (1 1,20MPa) and with the highest shear bond stregth accomplished when the 3M Resin Cement was the luting agent (14,16MPa). Higher values were also obtained with the porcelain discs and after the 180 days storage period. Mode of failure varied among the groups, with predominance of mixed fractures at the tooth/cement interface, and with a few cohesive porcelain and glass polymer fractures. It can be concluded that the Resin Cement (3M) and the procedure used offer reasonable strength on the porcelain and dentin site